2015
DOI: 10.5005/jp-journals-10003-1209
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Endoscopic Myringoplasty vs Conventional Myringoplasty

Abstract: Objective: To evaluate the efficacy of endoscopic myringoplasty and comparison with conventional myringoplasty. Materials and methods:Sixty cases of clinically diagnosed chronic suppu rative otitis media with dry central perforation were taken into account of which 30 cases were undergone endoscopic myringo plasty and 30 cases undergone conven tional myringoplasty. All patients were followed up on 3rd, 7th, 15th day, 6th weeks, 3rd and 6th months after surgery. Results:The tympanic membrane's perforation heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 4 publications
5
40
0
5
Order By: Relevance
“…Our primary search yielded a total of 8700 records. In the screening of the records by title, abstract and full‐text, we found 18 articles which met the eligibility criteria . We found two publications with identical cohorts of patients; therefore, we excluded the recently published one .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary search yielded a total of 8700 records. In the screening of the records by title, abstract and full‐text, we found 18 articles which met the eligibility criteria . We found two publications with identical cohorts of patients; therefore, we excluded the recently published one .…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies including 1179 interventions were deemed eligible for inclusion . Accrued results, in which endoscopic type I tympanoplasty was as effective as microscopic type I tympanoplasty in a homogenous dataset, indicated a 90.5% graft uptake rate in the endoscopic and 88.3% success rate in the microscopic group (OR: 1.21, CI: 0.82‐1.77; I 2 = 0.0%, P = 0.910) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…[2] In the study conducted by Kumar M, et al, in the endoscopy group all the patients rated their cosmetic outcome as excellent, whereas in the microscopic group 10 patients (33.3%) rated their cosmetic result as excellent, 16(53.3%) and 4(13.3%) patients rated their cosmesis as satisfactory and poor respectively. [4] In our study better cosmetic result in the microscopic groups as compared to these studies may be due to the fact that we used subcuticular continuous sutures for skin closure.…”
Section: Post Operative Cosmesismentioning
confidence: 43%
“…Average postoperative gain in the microscopic and endoscopic groups were 13.96 and 15.03 dB respectively. [4] In the study by Ambani K. et al, postoperatively hearing loss in the endoscopic group was within 30 dB was found in 38 of 40 patients(95%). [12] Complications There were no significant complications in either group.…”
Section: Graft Uptakementioning
confidence: 99%
See 1 more Smart Citation